2021
DOI: 10.1111/apha.13674
|View full text |Cite
|
Sign up to set email alerts
|

Microglia‐leucocyte axis in cerebral ischaemia and inflammation in the developing brain

Abstract: Development of the Central Nervous System (CNS) is reliant on the proper function of numerous intricately orchestrated mechanisms that mature independently, including constant communication between the CNS and the peripheral immune system. This review summarizes experimental knowledge of how cerebral ischaemia in infants and children alters physiological communication between leucocytes, brain immune cells, microglia and the neurovascular unit (NVU)—the “microglia‐leucocyte axis”—and contributes to acute and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 268 publications
(500 reference statements)
0
16
0
1
Order By: Relevance
“…In support, using LysM-eGFP mice, we found GFP positive myeloid cells in the hippocampus after infection. While leukocyte trafficking has been reported in several animal models of cerebral ischemia and inflammation in both neonatal and adult mice, contributing to acute and long-term brain injury, underlying mechanisms remain unclear (Rayasam et al, 2021). We previously showed monocyte and granulocyte infiltration to the brain 24 hours after cerebral hypoxia-ischemia (Smith et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In support, using LysM-eGFP mice, we found GFP positive myeloid cells in the hippocampus after infection. While leukocyte trafficking has been reported in several animal models of cerebral ischemia and inflammation in both neonatal and adult mice, contributing to acute and long-term brain injury, underlying mechanisms remain unclear (Rayasam et al, 2021). We previously showed monocyte and granulocyte infiltration to the brain 24 hours after cerebral hypoxia-ischemia (Smith et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Infiltration of leukocytes is an event often observed after blood-brain barrier (BBB) dysfunction, which is known to be associated with several neurological conditions (Rayasam et al, 2021). Therefore, we evaluated BBB permeability after S. epidermidis infection by measuring the plasma/brain ratio of glucose in the hippocampus of S. epidermidis-infected mice (Ek et al, 2015).…”
Section: Peripheral Immune Cells Infiltration Into the Hippocampus Fo...mentioning
confidence: 99%
“…These differences in the time course of M1/M2 polarization between studies are likely related to differences in species and model; for example, that the rodent HI model leads to a severe stroke-like pattern of damage. Interestingly, there is growing evidence from rodent studies that inflammation and microglial responses to HI can be modulated in a sex-dependent manner [ 45 ]. However, the present study was not powered to assess sex differences.…”
Section: Discussionmentioning
confidence: 99%
“…69 Changes in brain physiology, such as after injury or disease, often leading to cognitive deficits have been correlated with increased neutrophil activation and recruitment. 33,[70][71][72][73][74][75][76] However, very few studies have shown a direct link between the activity of neutrophils and cognitive deficits. One such study showed that the recruitment and activity of neutrophils to the meninges following subarachnoid hemorrhage led to cognitive decline associated with the injury.…”
Section: Under Ab Normal Conditions Neutrophil S C An D Irec Tly Aff...mentioning
confidence: 99%
“…Changes in brain physiology, such as after injury or disease, often leading to cognitive deficits have been correlated with increased neutrophil activation and recruitment 33,70–76 . However, very few studies have shown a direct link between the activity of neutrophils and cognitive deficits.…”
Section: Under Abnormal Conditions Neutrophils Can Directly Affect Co...mentioning
confidence: 99%